Long-term effects of a severe tropical cyclone on coral reef habitat and fish assemblages at the Whitsunday Islands, central Great Barrier Reef - Maya Srinivasan; Gemma F. Galbraith; Daniela M. Ceccarelli; Benjamin J. Cresswell; Sina J. Strähl; David H. Williamson (PLoS ONE, 2026)
Coral reef habitats and associated fish communities can be severely impacted by physical disturbances such as storms and cyclones, which can dramatically reduce live coral cover. However, rapid coral recolonisation and growth can lead to short-term recovery of both coral and fish assemblages. Here we examine the impact of a category 4 cyclone at the Whitsunday Islands (Cyclone Debbie in 2017). Changes in hard coral cover and the density, species richness and species composition of butterflyfishes and damselfishes were assessed over a 12-year period: 3 surveys prior to the cyclone (2012, 2014 and 2016), two surveys 8–19 months after (2017 and 2018) and another two surveys 5–6 years later (2022 and 2023). The percent cover of complex corals and massive/encrusting corals declined by 69% and 37% respectively between the pre-cyclone period and the two 8–19 months after the cyclone, with no significant recovery 5–6 years later. Density and species richness of both butterflyfishes and damselfishes declined significantly immediately after the cyclone, and these declines continued 5–6 years on. There was a shift in species composition in both fish families from a dominance of coral dependent species prior to the cyclone towards a dominance of macroalgal and rubble associated species. Species-level patterns were examined for the most abundant butterflyfish and damselfish species surveyed, and all but one species suffered long-term declines in density ranging from 31% to 85% over the period 2016–2023. The immediate and long-term declines included fishes both reliant and not reliant on live coral for habitat/food. Our study indicates that severe tropical cyclones can lead to short- and long-term declines in coral and fish assemblages, and rapid recovery should not be assumed. Given the potential for an increase in the frequency of severe cyclones with climate change, continued long-term monitoring is essential to examine the cumulative decadal effects of these disturbances.